Perancangan Dan Pengembangan Sunshield Handguard Sebagai Pelindung Tangan Pengendara Motor Berbasis Zero Energy - Dinda Dwi Aprilia; Achmad Ramzi; Tan Evan Tandiyono (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The rising number of motorcycle riders in Indonesia is accompanied by significant exposure to sunlight, which can cause discomfort, fatigue, and impaired concentration while riding. A rider's hands are particularly vulnerable to direct heat exposure. This study aims to design and develop the "Sunshield Handguard," a zero-energy hand protection device for motorcyclists—meaning it operates without requiring an electrical power source. The study employs the Research and Development (R&D) method, encompassing user needs identification, product concept design, prototype fabrication, and testing of the product's functionality and feasibility. The prototype is designed using lightweight, heat-resistant materials and is easily installed on various motorcycle models without interfering with steering or brake lever operation. Test results indicate that the Sunshield Handguard effectively reduces direct sunlight exposure on the hands and enhances riding comfort, while featuring a sturdy, ergonomic design. Furthermore, the zero-energy concept makes the product environmentally friendly and cost-effective, requiring neither operational costs nor complex maintenance. Thus, the Sunshield Handguard holds potential as a simple yet effective innovation for improving motorcyclist comfort and safety, particularly during rides in hot weather conditions.